Breadth and magnitude of antigen-specific antibody responses in the control of plasma viremia in simian immunodeficiency virus infected macaques. Issue 1 (December 2016) - Pahar, Bapi; Kenway-Lynch, Carys; Marx, Preston; Srivastav, Sudesh; LaBranche, Celia; Montefiori, David; Das, Arpita
Abstract Background Increasing evidence suggests an unexpected potential for non-neutralizing antibodies to prevent HIV infection. Consequently, identification of functional linear B-cell epitopes for HIV are important for developing preventative and therapeutic strategies. We therefore explored the role of antigen-specific immune responses in controlling plasma viremia in SIV infected rhesus macaques. Methods Thirteen rhesus macaques were inoculated either intravaginally or intrarectally with SIVMAC 251. Peripheral blood CD4+ T-cells were quantified. Plasma was examined for viremia, antigen specific IgG, IgA and IgM binding responses and neutralizing antibodies. Regions containing binding epitopes for antigen-specific IgG, IgM and IgA responses were determined, and the minimum size of linear Envelope epitope responsible for binding antibodies was identified. Results The presence of neutralizing antibodies did not correlate the outcome of the disease. In a few SIV-infected macaques, antigen-specific IgG and IgM responses in plasma correlated with decreased plasma viremia. Early induction and the breadth of antigen-specific IgG responses were found to be significantly correlated with the control of plasma viral load. Immunoglobulin classes share similar functional linear B-cell epitopes. SIV-specific linear envelope B-cell epitopes were found to be 12 amino-acids in length. Conclusions Early induction of combination of peptide-specific IgG responses were found to be responsible for the control of plasma viral load and indicative of disease outcome in SIV-infected rhesus macaques and might be important for the development of therapeutic strategies for control or prevention of HIV/AIDS.